2013
DOI: 10.1098/rsif.2013.0747
|View full text |Cite
|
Sign up to set email alerts
|

An encapsulated drug delivery system for recalcitrant urinary tract infection

Abstract: One of the hallmarks of urinary tract infection, a serious global disease, is its tendency to recur. Uropathogenic bacteria can invade cells lining the bladder, where they form longer-term intracellular reservoirs shielded from antibiotics, re-emerging at a later date to initiate flare-ups. In these cases, only lengthy systemic antibiotic treatment can eradicate all the reservoirs. Yet, long courses of antibiotics are not ideal, as they can lead to side effects and an increase in antibiotic resistance. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The protocol for the extended antibacterial assay was similar to that previously reported [32]. Briefly, an overnight culture of E. faecalis clinical strain EF36 (isolated directly from a patient with chronic UTI [12], in TSB was adjusted to the equivalent of a 0.5 McFarland standard using CnT Prime bladder epithelial media (CELLnTEC, Switzerland).…”
Section: Determination Of Extended Antibacterial Activity Against E Faecalismentioning
confidence: 99%
“…The protocol for the extended antibacterial assay was similar to that previously reported [32]. Briefly, an overnight culture of E. faecalis clinical strain EF36 (isolated directly from a patient with chronic UTI [12], in TSB was adjusted to the equivalent of a 0.5 McFarland standard using CnT Prime bladder epithelial media (CELLnTEC, Switzerland).…”
Section: Determination Of Extended Antibacterial Activity Against E Faecalismentioning
confidence: 99%
“…There are pilot data showing the feasibility of loading an antibiotic into a non-cell-toxic microcapsule that can both penetrate bladder cells and provide slow release of the drug that retains its bactericidal properties. 67 This system has been developed for the delivery of high doses of antibiotic to treat recalcitrant UTIs. The capsules have been prepared with coaxial electrohydrodynamic forming technology, which has shown considerable promise for the production of fibers and particles at the micro- and nanoscale.…”
Section: Targeted Bladder Ddssmentioning
confidence: 99%
“…Electrospraying has been investigated thoroughly as a potential technique for pharmaceutical applications [ 19 ] and more specifically for dissolution enhancement of water-insoluble drugs by facilitating preparation of the drug delivery system at reduced size [ 20 ], where a higher surface area to volume ratio greatly favours the rate at which the incorporated drug is released [ 21 , 22 ]. In a study by Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
“…Electrospraying has been investigated thoroughly as a potential technique for pharmaceutical applications [19] and more specifically for dissolution enhancement of water-insoluble drugs by facilitating preparation of the drug delivery system at reduced size [20], where a higher surface area to volume ratio greatly favours the rate at which the incorporated drug is released [21,22]. In a study by Zhang et al [23], it was reported that using coaxial electrospraying for preparation of a griseofulvin formulation using Eudragit L100 as an encapsulating carrier significantly enhanced the dissolution and absorption behaviour of the poorly water-soluble drug.…”
Section: Introductionmentioning
confidence: 99%